Reactions of root plasma membrane redox activities in iron-deficient cucumber plants after application of ionic and chelated copper - Boycheva, Svetlana V.; Babalakova, Nadejda K. (Acta Biologica Szegediensis, 2006)
The effects of ionic (CuSO4) and chelated forms of copper (Cu(II)HEDTA, where HEDTA is N-(2-hydroxyethyl) ethylenediamine triacetic acid, applied at micromolar concentrations in nutrient solutions of cucumber plants grown hydroponically under conditions of iron deficiency (–Fe), were studied. Changes of plasma membrane reductase activity (PMRA) of intact roots after treatment with ionic or chelated copper were followed in (+Fe) and (–Fe) cucumber plants. Iron deprivation in nutrient solution provoked a great increase of ferric-chelate reductase activity (with substrate of Fe(III)HEDTA) and accelerated the cupric-chelate reductase activity (measured with Cu(II)Citrate as an electron acceptor) as well as the hexacyanoferrate(III) [HCF(III)] reductase activity. Continuous application of cupric ions in solutions of iron-deficient plants resulted in a dramatic inhibition of Fe(III)HEDTA and Cu(II)Citrate reductase activity. The reductase activity in iron-deficient cucumber roots, measured with HCF(III), was inhibited to a lower extent after cupric ions treatment. On the other hand, the cupric-chelate Cu(II)HEDTA, applied at the same concentrations in solutions with (–Fe) plants, maintained the high stimulation of plasma membrane ferric-chelate and cupric-chelate reductase activity and produced additional acceleration of HCF(III) reduction by cucumber roots. The treatment with Cu(II)HEDTA improved the growth and root PMRA as well as other iron-deficiency stress responses of cucumber plants.